Kilomet og dens fæller - Sandbæk Geertsen, Line (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2024)
This paper explores the prevalence of the variant singular form kilomet of the Danish word kilometer, as well as centimet and millimet. These variants are not considered correct by many speakers. The theoretical background includes Hock’s (2021) definition of analogical change. The history of kilometer shows two major orthographical/morphological disagreements: (1) When the metric system was introduced into Danish, the words had several variants with number distinctions; and (2) from the 1960s onward, kilometer was subject to backformation where the final syllable was reanalysed as a plural marker. I collected data from 16 informants through a read aloud task and a semi-structured interview. The results show that half of the informants used the kilomet variant to some extent, and only one used it exclusively. One informant used the centimet variant and one the millimet variant. The attitudes towards the kilomet variant varied widely. I present several speculative reasons for why kilometer is the only of the -meter words to have undergone a backformation. These include morphophonological structure, frequency of use and paradigmatic strength. The prevalence of the kilomet variant in my data and the recent history of kilomet suggests that it should be studied further undergo further, and perhaps be properly considered for inclusion in various dictionaries in written form.